ANALISIS KANDUNGAN LOGAM TIMBAL PADA MINYAK SEBELUM DAN SESUDAH DIGUNAKAN PEDAGANG GORENGAN DI KELURAHAN BENOA - Lutfidiani, Raissa; Suryadhi, Made Ayu Hita Pretiwi (ARCHIVE OF COMMUNITY HEALTH; Vol 8 No 3 (2021): Desember 2021DO - 10.24843/ACH.2021.v08.i03.p14, 2022)
ABSTRACT Fried foods are snacks that are often consumed by society because in addition to being cheap, delicious, and easy to get, fried foods can also provide energy intake between meals. Fried food merchants who are usually located on the side of the road could risk of being contaminated with lead in the cooking oil used from motor vehicle fumes emissions. This research aims to determine the lead content in cooking oil before and after being used by fried food merchants in Benoa Village. The research design used is a descriptive survey research and sampling on this study used a purposive sampling technique. Each merchant will be tested of cooking oil before fried, cooking oil after fried on Friday and Saturday, cooking oil after fried without ingredients to make the last fry, and the fried food. A laboratory examination used the Atomic Absorption Spectrophotometry (AAS). Laboratory results showed the concentration of heavy metal lead (Pb) contained in all types of oil has exceeded the maximum metallic Pb limit in the oil regulated in SNI 7387:2009. While the concentration of Pb contained in fried does not exceed the maximum Pb limit as regulated in BPOM RI Regulation Number HK.00.06.1.52.4011. Keywords: Lead, Cooking Oil, Fried Food